Influência da realização de uma tarefa secundária e do nível de experiência no desempenho tático de jogadores de futebol durante pequenos jogos - Vitor Hugo Santos Rezende (2023)
The present study aimed to compare the dual-task cost and the level of experience in the tactical performance of soccer players during small-sided games (SSG). The study included 36 less experienced soccer players (U-13) and 36 more experienced athletes (U-17), totalling 72 athletes from two soccer teams in Belo Horizonte. The participants performed two days of familiarization to know all experimental procedures and team composition. Two days after the familiarization, the participants performed, in a randomized and balanced way, four experimental conditions composed of the following protocols: 1) Simple Task (TS), 2) Motor Dual Task (MDT), 3) Cognitive Dual Task 1 (CDT1), 4) Cognitive Dual Task 2 (CDT2). The four experimental conditions were performed during (SSG) with the structure GR+3 vs. 3+GR, which were filmed for the tactical evaluation of the players through the Tactical Evaluation System in Football (FUTSAT). To evaluate the positional data, Global Positioning System (GPS) equipment was used. Variables were expressed as mean and standard deviation. Data normality was verified by the Kolmogorov-Smirnov test. The variables obtained through the FUT-SAT and the individual variables obtained through the GPS were analyzed using a MANOVA. Collective variables obtained by GPS were analyzed using two-way mixed ANOVA (experimental category and protocol) and Bonferroni post hoc. MANOVA showed an effect of protocol, category and the interaction between category and protocol on tactical performance (p<0.001). Offensive, defensive and general tactical performances were higher in the TS protocol than in other protocols (p<0.001). Comparing the categories, the U-17 category had the highest percentage of time in in-phase and anti-phase width synchronization (p=0.007), and the lowest cost in penetration (p=0.007) and concentration (p=0.025) tactical principles, the U-17 and U-13 showed the highest percentage of time in synchronization in in-phase length (p=0.001), and lowest cost in tactical principles off-the-ball space (p=0.007), delay (p=0.001), and defensive balance (p=0.025). Comparing the protocols, the MDT presented a higher cost in synchronizing in-phase (p<0.001) and anti-phase width (p<0.001), in defensive tactical performance (p=0.006) and the tactical principle of off-the-ball space (p=0.002). There was no significant difference between the CDT1 and CDT2 protocols (p>0.05). The results suggest that the secondary task generates a cost to tactical performance, the MDT protocol seems to generate a higher cost to the performance than the CDT1 and CDT2 protocols. The U-17 category has a lower cost in actions with the ball and the U-13 category has a lower cost in defensive actions close to the ball.